Evaluation of Some Properties of Acrylic Resin Denture Base Reinforced with Calcium Carbonate Nano-Particles - Jawad Mikael; Salem Al-Samaraie; Fahd Ikram (Erbil Dental Journal)
Background and objectives: Radiolucency of poly methyl methacrylate denture base resin is of great concern, and many approaches have been used to make acrylic resin dentures more radiopaque.The purpose of this study was to prepare a modified heat cure ploy methyl methacrylate denture base resin by incorporation of different weight percentages (2%, 3%, 4%, 5%, and 6%) of CaCO3 nanofiller particles, to increase its radiopacity.